Compact Design of 10 kW Proton Exchange Membrane Fuel Cell Stack Systems with Microcontroller Units - Hsiaokang Ma; Weiyang Cheng; Fuming Fang; Chinbing Hsu; Chengsheng Lin (Energies, 2014)
In this study, fuel, oxidant supply and cooling systems with microcontroller units (MCU) are developed in a compact design to fit two 5 kW proton exchange membrane fuel cell (PEMFC) stacks. At the initial stage, the testing facility of the system has a large volume (2.0 m × 2.0 m × 1.5 m) with a longer pipeline and excessive control sensors for safe testing. After recognizing the performance and stability of stack, the system is redesigned to fit in a limited space (0.4 m × 0.5 m × 0.8 m). Furthermore, the stack performance is studied under different hydrogen recycling modes. Then, two similar 5 kW stacks are directly coupled with diodes to obtain a higher power output and safe operation. The result shows that the efficiency of the 5 kW stack is 43.46% with a purge period of 2 min with hydrogen recycling and that the hydrogen utilization rate µf is 66.31%. In addition, the maximum power output of the twin-coupled module (a power module with two stacks in electrical cascade/parallel arrangement) is 9.52 kW.